Osteoarthritis Progress in Basic Research and Treatment - Chen, Qian (IntechOpen, 2015)
The most common form of arthritis is osteoarthritis (OA), which most often affects the hip, knee, foot and hand. The degeneration of joint cartilage and changes in underlying bone and supporting tissues such as ligament leads to pain, stiffness, movement problems and activity limitations. This book, containing three major sections in OA research and therapy, is an update of the book Osteoarthritis - Diagnosis, Treatment and Surgery published by InTech in 2012. The authors are experts in the osteoarthritis field, which include biologists, bioengineers, clinicians, and health professionals. The scientific content of the book will be beneficial to patients, students, researchers, educators, physicians, and health care providers who are interested in the recent progress in osteoarthritis research and therapy.